Analgesic and anti-inflammatory potential of ethanolic extract from Serjania erecta leaves - Bernal, Laura Priscila Toledo; Leitão, Maicon Matos; Radai, Joyce Alencar Santos; Cardoso, Claudia Andrea Lima [UNESP]; Lencina, Joyce dos Santos; Fraga, Thiago Leite; Arena, Arielle Cristina [UNESP]; Silva-Filho, Saulo Euclides; Kassuya, Cândida Aparecida Leite (Elsevier, 2023)
Ethnopharmacological relevance: The infusion of Serjania erecta Radlk (Sapindaceae) (popular name “cipó-cinco-folhas”) leaves is used in popular medicine to treat back pain. The anti-inflammatory, anti-hyperalgesic and anti-nociceptive properties of the ethanolic extract from S. erecta leaves (EESE) has not been yet completely clarified. Aim of the study: The present study investigated the anti-hyperalgesic, anti-nociceptive and anti-inflammatory properties of EESE in experimental models in mice. Material and methods: EESE was fractionated by chromatographic techniques and the compound was identified by nuclear magnetic resonance (NMR), infrared (IR) spectrum, ultraviolet (UV) methods. Mice received a single dose of EESE by oral route (30, 100, and 300 mg/kg, p.o.) and were submitted to nociception induced by formalin, pleurisy induced by carrageenan and peritonitis induced by zymosan models. Mice also received EESE (30 and 100 mg/kg, p.o.) for 22 days in Complete Freund Adjuvant (CFA) model and another group received EESE for 7 days (30 and 100 mg/kg, p.o.) in pleurisy induced by Bacillus Calmette-Guerin (BCG). The cytotoxicity (MTT), phagocytic and chemotactic inhibitory activities of EESE were performed in in vitro assays. Results: The fractionation of EESE led to the identification of kaempferol-3-O-α-L-rhamnopyranoside. The oral administration of all doses of EESE decreased the nociceptive response induced by formalin. EESE significantly inhibited leukocyte migration in carrageenan-induced pleurisy and zymosan peritonitis models. The daily administration of EESE during for 7 days inhibited the leukocyte migration and the mycobacteria growth of pleural material obtained from animals which received BCG. EESE significantly reduced edema, cold allodynia and mechanical hyperalgesia responses induced by CFA. EESE did not induce cytotoxicity, and also decreased the leukocyte phagocytic activity, as well as, neutrophil chemotaxis. Conclusions: EESE showed analgesic and anti-inflammatory properties in acute and persistent experimental models in mice. EESE also reduced in vitro leukocyte chemotaxis and phagocytic activity without inducing cytotoxicity. The continuous oral treatment with EESE was effective against hyperalgesia and inflammation and these results could explain the popular use of S. erecta as an analgesic natural agent.
Keywords: Bacillus calmette-guerin (BCG); Complete freund adjuvant (CFA); Mice; Pain; Sapindaceae; Serjania erecta